Private branch exchanges for connection to public switched telephone networks run by certain public telecommunication operators. Simple call-routing mode (SCRM). Specification for the simple call-routing mode of PBX operation, with terminating stations treated as an entirety Part 6-6.1, (30th September 1988) - British Standards Institution
No abstract available